Scarlet Shawls / Mohd Fakhruddin Zakaria ... [et al.] - Zakaria, Mohd Fakhruddin; Ainudin Fitri, Ainur Fitriah; Mohd Razali, Noraliya Syamimi; Emlih, Narnienia Nastannya (2021)
Based on the overall report, the conclusion that can be made is that we have opened a business company called “Scarlet Shawls”. We have chosen the name scarlet as the company name because it carries meaning to courage, strength, passion, and joy. Our company has been selling products namely shawls which consist of various types of high-quality fabrics. Our target market is women and teenage girls. We also produce products that have their own differences to compete with other companies. Among the varieties of our products that are able to provide a competitive advantage are trendy patterns, waterproof and seasonal limited. In terms of the finances of our business, all data such as sales, profit, cash flow and return on investment will be recorded in the cash flow statement. Within 5 years of our company, our total sales were RM2,405,314.09. The profit of our company in 5 years is RM556,345.88 excluding capital. The total capital we need to start and grow a business is RM72,795.45. We have used this capital to finance all expenses such as office furniture, office equipment, signboards, machines, and others. Overall, the form of company we run is a partnership. The main owner of this company is Ainur Fitriah Binti Ainudin Fitri who is the general and administration manager. Next, the main staff of the company is Narnienia Nastannya Binti Emlih who is the marketing manager, then Noraliya Shamimi Binti Mohd Razali who is the operations manager and finally Mohd Fakhruddin Bin Zakaria who is the financial manager. The main achievement of our company is that we have successfully produced very unique and high-quality products to compete with other business companies. We also managed to produce a waterproof type of shawl. Our business location is located at MM 171, Medan Mewah Office Shop, 26700 Muadzam Shah, Pahang held under HSD 4511, PT 482, Bandar Muadzam Shah 1, Rompin District, Pahang. We also do business online and on social media.